Patriotic Education of Primary School Children in System of Additional Education - Y. V. Makarchuk (Tsentr nauchnykh i obrazovatelnykh proektov, 2017)
The problem of patriotic education as one of the priorities in the educational system of the school is considered. The research urgency is caused by the fact that the events of the end of the 20th - beginning of the 21st century led to the loss of valuable experience in this field, therefore in educational institutions there are a variety of programs of patriotic education of children and youth. It is shown that in spite of all the efforts made at the school, the level of patriotic education of students remains low, especially for motivational and behavioural components of patriotic education. It is indicated that the school mainly organizes teaching activities, which reflects in the prevalence of cognitive-intellectual component in patriotic education of children. It is proved that the formation of motivational, consumer, behavioural and volitional components of patriotism is effectively realized in the system of additional education. The experiment is described on the application of a number of methods of formation of patriotism among the younger students in the residence club. It is noted that the work on patriotic education in the club suggests the possibility of development and application of different methodologies aimed at the development of patriotic attitude not only towards Russia in general, but also to the homeland, as well as the family, school, nature etc.